Quantifying credit gaps using survey data on discouraged borrowers - Ozan E. Akbas; Frank Betz; Luca Gattini (European Investment Bank (EIB), 2023)
The credit gap in this study is given by the financing needs of firms that are bankable but discouraged from applying for a loan. To quantify the credit gap, we combine a scoring model that assesses the creditworthiness of discouraged firms with a credit allocation rule. Our study covers 35 emerging markets and developing economies and uses the 2018-2020 EBRD-EIB-World Bank Enterprise Survey. We show that on average discouraged firms are less creditworthy than successful applicants. Nonetheless, the share of bankable discouraged firms is large, suggesting inefficient credit rationing. The baseline results point to an aggregate credit gap of 8.4% of GDP with significant variation across countries. SMEs account for more than two-thirds of the total, reflecting both their contribution to economic activity and the fact that they are more likely to be credit-constrained.
Keywords: D22; D45; E51; G21; G32; 330; credit rationing; discouraged borrowers; firm-level data; EMDEs